SYSTEMATIC REVIEW OF STUDIES MAMAE CANCER: A NURSING REVIEW - Tri Nurhidayati; Desy Ariyana Rahayu (Universitas Muhammadiyah Semarang, 2017)
Breast cancer is a disease caused by abnormal growth of tissue cells of the body that turn into cancer cells. Anytype of treatment for breast cancer can lead to psychological problems. Since now there are not a lot of studies Mamae cancer a nursing review. The systematic review is an integral part of evidence based health care. One of the best definitions of evidence based medcines (which can be applied to health care in general) “...is theintegration of best reserach care in general with clinical expertise and patient values (Spector, 2006). This is acomprehensive definit ion that doesn’t just include the results of best studies, but also considers clinical expert iseand the patients needs. This systematic review is intended to be critical analysis of evidence supports. It is important to note that this in a evolving review that will continually change as more research becomes available. Keywords: Mamae Cancer, Systematic Review